Synthetic Stimulator of Interferon Genes (STING) Agonists Induce a Cytokine-Mediated Anti-Hepatitis B Virus Response in Nonparenchymal Liver Cells - Pimkova Polidarova, Marketa; Vanekova, Lenka; Brehova, Petra; Dejmek, Milan; Vavrina, Zdenek; Birkus, Gabriel; Brazdova, Andrea (ACS infectious diseases, 2023)
Chronic hepatitis B (CHB) remains a major public health problem worldwide, with limited treatment options, but inducing an antiviral response by innate immunity activation may provide a therapeutic alternative. We assessed the cytokine-mediated anti-hepatitis B virus (HBV) potential for stimulating the cyclic GMP-AMP synthase-stimulator of interferon genes (STING) pathway using STING agonists in primary human hepatocytes (PHH) and nonparenchymal liver cells (NPCs). The natural STING agonist, 2',3'-cyclic GMP-AMP, the synthetic analogue 3',3'-c-di(2'F,2'dAMP), and its bis(pivaloyloxymethyl) prodrug had strong indirect cytokine-mediated anti-HBV effects in PHH regardless of HBV genotype. Furthermore, STING agonists induced anti-HBV cytokine secretion in vitro, in both human and mouse NPCs, and triggered hepatic T cell activation. Cytokine secretion and lymphocyte activation were equally stimulated in NPCs isolated from control and HBV-persistent mice. Therefore, STING agonists modulate immune activation regardless of HBV persistence, paving the way toward a CHB therapy.
Keywords: herpesvirus B; Humans; interferony; Herpesvirus 1, Cercopithecine; cytokiny; nonparenchymal liver cells; lidé; Interferons; zvířata; HBV-persistent mouse model; myši; Mice; antiviral immunity; hepatitida B; Hepatitis B; Cytokines; STING; Hepatocytes; Animals; hepatocyty; Chronic Hepatitis B; cytokine